Role of Endolysosomes in Severe Acute Respiratory Syndrome Coronavirus-2 Infection and Coronavirus Disease 2019 Pathogenesis: Implications for Potential Treatments - Khan, Nabab; Chen, Xuesong; Geiger, Jonathan D. (Frontiers in Pharmacology, 2020)
Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is an enveloped, single-stranded RNA virus. Humans infected with SARS-CoV-2 develop a disease known as COVID-19 with symptoms and consequences including acute respiratory distress syndrome (ARDS), cardiovascular disorders, and death. SARS-CoV-2 appears to infect cells by first binding viral spike proteins with host protein angiotensin-converting enzyme 2 (ACE2) receptors; the virus is endocytosed following priming by TMPRSS2 (transmembrane protease, serine 2). The process of virus entry into endosomes and its release from endolysosomes are key features of enveloped viruses. Thus, it is important to focus attention on the role of endolysosomes in SARS-CoV-2 infection. Indeed, coronaviruses are now known to hijack endocytic machinery to enter cells such that they can deliver their genome at replication sites without initiating host detection and immunological responses. Hence, endolysosomes might be good targets for developing therapeutic strategies against coronaviruses. Here, we focus attention on the involvement of endolysosomes in SARS-CoV-2 infection and COVID-19 pathogenesis. Further, we explore endolysosome-based therapeutic strategies to restrict the SARS-CoV-2 infection and COVID pathogenesis.